Hosts and environment overshadow spatial distance as drivers of bat fly species composition in the Neotropics. (20th November 2019) - Eriksson, Alan; Doherty, Jean‐François; Fischer, Erich; Graciolli, Gustavo; Poulin, Robert
Abstract: Aim: Determine the relative influence of geographical distance, environmental differences, and host species composition on the similarity of bat fly species composition. Location: Neotropics. Taxon: Bats (Chiroptera: Phyllostomidae) and bat flies (Diptera: Streblidae). Methods: Abundance data on bats and ectoparasites were obtained from published studies. The relative influences of environmental variation (annual precipitation, temperature seasonality, elevation, and NDVI), host species composition, and geographic distance on parasite community composition were analysed with Generalized Dissimilarity Modelling and variance partitioning. Additionally, we evaluated the influence of these environmental variables and geographic distance on host species composition. Results: Our model explains 45.3% of the variance in the dissimilarity of bat fly species. Host species composition had the most significant influence on bat fly species composition across communities, followed by environmental effects. Variance partitioning showed that host species composition explained 14.9% and environmental characteristics explained 10.3% of the variance in bat fly species dissimilarity. Geographical distance alone had a negligible effect as it accounted for only 0.007% of the variance in bat fly species composition. Host species composition was mainly influenced by geographic distance (18.0%) and secondarily by environmental variables (9.8%). The most important environmental variables influencing parasite and host species composition were annual precipitation and temperature seasonality, respectively. Main Conclusions: The lack of relationship between geographical distance and bat fly species composition may reflect either the high mobility or the high dispersal capacity of bat flies, or a combination of these. Alternatively, it could reflect a taxonomic artefact. Environmental differences seem to directly affect bat flies, as opposed to affecting them indirectly through their impact on the hosts. Our results support the fundamental role that host species composition plays in determining the species composition of highly host‐specific parasites. However, we argue that host specificity is not the only trait impacting ectoparasite species composition.